Diurnal rhythm and stress regulate dendritic architecture and spine density of pyramidal neurons in the rat infralimbic cortex - Perez-Cruz, Claudia; Simon, Mária; Flügge, Gabriele; Fuchs, Eberhard; Czéh, Boldizsár (Behavioural brain research, 2009)
The medial prefrontal cortex (mPFC) participates in several higher order cognitive functions and is involved in the regulation of the stress response. The infralimbic cortex (ILC), the most ventral part of the mPFC, receives a strong afferent input from the master circadian pacemaker, the suprachiasmatic nucleus. This fact raises the possibility that, similarly to stress, the diurnal rhythm may affect structural plasticity of neurons in the ILC. Here we investigated, whether diurnal changes in combination with immobilization stress have any impact on the dendritic morphology of layer III pyramidal neurons in the ILC. Prefrontal cortices were collected from control rats at two different time points of the diurnal cycle (12 h apart), and from rats exposed to 1-week of daily restraint stress either during their active or resting period. Dendritic architecture and spine density of Golgi–Cox stained neurons were digitally reconstructed and analyzed. We found that in control rats during the active period, the basilar dendrites were always longer and more complex, and had more spines than during the resting period. Similar although less pronounced diurnal differences exist in the apical dendrites. Stress affected dendritic architecture in a way that the diurnal differences either disappeared or became reduced in their magnitude. Our findings indicate that the diurnal rhythm has a unique impact on the structural plasticity of pyramidal cells in the ILC and that stress interferes with this form of neuroplasticity.